Symbolism of Ismullah and Local Wisdom of Cirebon: Visualization of Perfect Prayer in the Cirebon Kaprabonan Manuscript - Basiran Basiran; Riki Nasrullah (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2025)
Islamic manuscripts play a crucial role in preserving the intellectual and spiritual heritage of Muslim communities, including the symbolic and esoteric dimensions of Islamic education. However, studies on Syattariyah manuscripts in Java, especially those exploring symbolic visualization of ritual practices remain limited and tend to focus either on philological description or doctrinal transmission rather than interpretive meaning. This study aims to analyze the symbolic construction of the Perfect Prayer (Sholat Sempurna) within the Kaprabonan manuscript of Cirebon and explore its relevance to contemporary spiritual education. A qualitative research design was employed, using manuscript analysis, content analysis, and hermeneutic interpretation guided by Ernst Cassirer's philosophy of symbolic forms. The analysis demonstrates that each stage of the prayer corresponds to symbolic elements of the Ismullah (الله): standing aligns with Alif, bowing with the first Lam, prostration with the second Lam, and sitting with Ha. This structure forms a symbolic framework linking bodily movement, spiritual consciousness, and metaphysical unity with God. The findings indicate that this symbolic system functions not only as a ritual framework but also as a pedagogical model for cultivating spiritual awareness, ethical balance, and contemplative discipline. Furthermore, the symbolic interpretation of Sholat Sempurna reflects the balanced and inclusive values of Islamic moderation (wasathiyah), connecting spiritual depth with cultural wisdom and social harmony. This study contributes to current scholarship in Islamic education, Sufi studies, and religious symbolism by demonstrating how local manuscript traditions can inform contemporary discourse on spirituality, tolerance, and character formation.